CD38: A Significant Regulator of Macrophage Function - Li, Wentao; Li, Yanling; Jin, Xi; Liao, Qianjin; Chen, Zhifang; Peng, Honghua; Zhou, Yanhong (Frontiers in Oncology, 2022)
Cluster of differentiation 38 (CD38) is a cell surface glycoprotein and multifunctional extracellular enzyme. As a NADase, CD38 produces adenosine through the adenosine energy pathway to cause immunosuppression. As a cell surface receptor, CD38 is necessary for immune cell activation and proliferation. The aggregation and polarization of macrophages are affected by the knockout of CD38. Intracellular NAD+ levels are reduced by nuclear receptor liver X receptor-alpha (LXR) agonists in a CD38 dependent manner, thereby reducing the infection of macrophages. Previous studies suggested that CD38 plays an important role in the regulation of macrophage function. Therefore, as a new marker of macrophages, the effect of CD38 on macrophage proliferation, polarization and function; its possible mechanism; the relationship between the expression level of CD38 on macrophage surfaces and disease diagnosis, treatment, etc; and the role of targeting CD38 in macrophage-related diseases are reviewed in this paper to provide a theoretical basis for a comprehensive understanding of the relationship between CD38 and macrophages.